2018
DOI: 10.22456/1679-9216.89400
|View full text |Cite
|
Sign up to set email alerts
|

Surgery-Induced Changes in Erythrocyte and Plasma Lipid Peroxidation, Enzymatic and Non-Enzymatic Antioxidants of Female Rats: Protective Role of Heparin and Pentoxifylline

Abstract: Background: Intra abdominal adhesions are a complication that occurs after many abdominal surgical procedures, especially gynecological operations. These complications occur by irritating the peritoneum due to such circumstances as infection or surgical trauma, and are considered a pathological part of the healing process of peritoneal injury. It manifests itself with symptoms such as pain, intestinal or urethral obstruction and abdominal abscesses. Oxidative stress due to adhesions plays an important role on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Previous studies have identified reperfusion as the major cause of tissue damage (Ünsal et al, 2006). In Simsek, Durmus, Yildiz, and Ozcelik (2018) in a study on surgery-induced intra-abdominal adhesions indicated the protective roles of heparin and pentoxifylline to prevent adhesions and reducing oxidative stress (Simsek et al, 2018). Recent studies have demonstrated that reperfusion can cause a noticeable increment in the overgeneration of lipid peroxidation, nitric oxide and germ cell apoptosis (Yuluğ et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have identified reperfusion as the major cause of tissue damage (Ünsal et al, 2006). In Simsek, Durmus, Yildiz, and Ozcelik (2018) in a study on surgery-induced intra-abdominal adhesions indicated the protective roles of heparin and pentoxifylline to prevent adhesions and reducing oxidative stress (Simsek et al, 2018). Recent studies have demonstrated that reperfusion can cause a noticeable increment in the overgeneration of lipid peroxidation, nitric oxide and germ cell apoptosis (Yuluğ et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Simsek, Durmus, Yildiz, and Ozcelik (2018) in a study on surgery-induced intra-abdominal adhesions indicated the protective roles of heparin and pentoxifylline to prevent adhesions and reducing oxidative stress (Simsek et al, 2018). Boettcher et al (2016) described the treatment effects of anti-thrombotic drugs such as alteplase, enoxaparin and heparin and indicated the reduction in testicular damage after using these drugs (Boettcher et al, 2016).…”
Section: Testicular Ischaemia Reperfusion Caused By Torsion Detorsionmentioning
confidence: 99%
“…Although studies have demonstrated anti-adhesive effects of anticoagulants such as hirudin [ 186 ], heparin [ 187 , 188 ], DMSO [ 189 ], and thrombolytic protein from cobra venom [ 190 ], some studies have shown that the effects are ambiguous [ 185 ]. Therefore, it seems that more research is needed to prove the anti-adhesion effects of anticoagulants.…”
Section: Various Strategies Of Anti-adhesionmentioning
confidence: 99%
“…The other regimen is to apply drugs/agents to suppress fibrous band formation and fibrin deposition . Generally, they could be divided into three main categories: anti-inflammatory drugs, such as ibuprofen and aspirin; anticoagulants, , such as heparin and dimethyl sulfoxide (DMSO); and fibrinolytic agents, such as N -acetyl- l -cysteine and streptokinase . However, as the drugs usually experience short retention time in the abdominal cavity, multiple doses are required, which may bring undesired adverse effects and restrict the clinical applicability. , In this scenario, combining these two regimens could compensate their disadvantages while keeping their strengths, resulting in safe and efficient anti-adhesive materials …”
Section: Introductionmentioning
confidence: 99%